"A gente segura um na mão do outro” compreensões sobre saúde mental dos Tapuya Kariri da Aldeia de Gameleira do Ceará - Carvalho, Socorro Taynara Araújo (2024)
Mental health is a complex and multifaceted concept that permeates several interconnected aspects, namely social, cultural, physiological and historical. Conceptions about mental health vary, as they are crossed by sociocultural, historical, material and symbolic aspects that organize the realities of diverse societies around the world. When it comes to indigenous peoples, although there is no single indigenous identity, as there are sociocultural differences that distinguish each ethnic group, they generally understand changes in health based on manifestations arising from spiritual and natural forces. Thus, the disease is not conceived only as an organic dysfunction, but as a disturbance of social, physical and cosmic forces. The present study aims to analyze the understanding of mental health of Tapuya Kariri indigenous people from the Gameleira Village in Ceará. Its specific objectives are: to learn about the history of the village; analyze understandings of mental health; investigate factors of suffering that affect mental health and learn about formal and informal mental health care strategies carried out in the traditional territories of the Tapuya Kariri of the Gameleira Village in Ceará. This is a qualitative research, of the action research type, in which conversations and semi-structured interviews were carried out, with people originating from the Tapuya Kariri de São Benedito territories. The Circles were recorded in audio format and transcribed, which will be analyzed using Content Analysis by Laurence Bardin. From the analysis of the information produced, three categories emerged, namely: conceptions about indigenous mental health, factors of suffering, SUS operations in indigenous territories. These were central elements in collective constructions in culture circles and are essential in the discussion of indigenous health. From the analysis of data from the conversation held with the Tapuyas Kariri, four categories emerged, which 12 point to understandings of indigenous mental health: experiences of psychological suffering, ancestral conceptions about mental health, factors causing indigenous suffering, SUS performance in the territory of the Tapuya Kariri. Therefore, it is necessary to understand populations' conceptions of health, considering their social, cultural and political aspects. We can make popular knowledge an ally of scientific knowledge, resulting in the creation of new knowledge, which will enable a new vision of the health-disease binomial.